2018
DOI: 10.1016/j.neubiorev.2018.10.001
|View full text |Cite
|
Sign up to set email alerts
|

The aversive brain system of teleosts: Implications for neuroscience and biological psychiatry

Abstract: Defensive behavior is a function of specific survival circuits, the "aversive brain system", that are thought to be conserved across vertebrates, and involve threat detection and the organization of defensive responses to reduce or eliminate threat. In mammals, these circuits involve amygdalar and hypothalamic subnuclei and midbrain circuits. The increased interest in teleost fishes as model organisms in neuroscience created a demand to understand which brain circuits are involved in defensive behavior. Telenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 163 publications
(211 reference statements)
0
18
0
Order By: Relevance
“…It is made The copyright holder for this preprint this version posted November 25, 2020. ; https://doi.org/10.1101/2020.11.24.396887 doi: bioRxiv preprint Npas4a Expression in Fear Learning ISH analysis showed that npas4a expression was significantly higher in reactive fish in the Dm, Dl, and Vs (Figures 2A-C). The Dm (BLA), Dl (HIP), and Vs (BNST) are key sites of experience-dependent plasticity and integral to fear learning and memory across species (32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is made The copyright holder for this preprint this version posted November 25, 2020. ; https://doi.org/10.1101/2020.11.24.396887 doi: bioRxiv preprint Npas4a Expression in Fear Learning ISH analysis showed that npas4a expression was significantly higher in reactive fish in the Dm, Dl, and Vs (Figures 2A-C). The Dm (BLA), Dl (HIP), and Vs (BNST) are key sites of experience-dependent plasticity and integral to fear learning and memory across species (32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…We then quantified npas4a and gabbr1a forebrain expression to investigate their potential link with differences in conditioned fear responses between alternative stress coping styles. We predict that an increased conditioned fear response in reactive zebrafish will be associated with increased expression of neural plasticity-related genes in the dorsal and medial portions of the dorsal telencephalon (Dm, Dl) and the dorsal, ventral, and supracomissural portions of the ventral telencephalon (Vd, Vv, Vs), putative homologues of the mammalian basolateral amygdala, hippocampus, striatum, lateral septum, and bed nucleus of the stria terminalis, respectively (32)(33)(34)(35).…”
Section: Npas4a Expression In Fear Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…In zebrafish, extracellular 5-HT levels were increased after CAS exposure , an effect that can be related to decreased 5-HT uptake (Maximino et al, 2014) and/or decreased monoamine oxidase activity (Lima-Maximino et al, 2020;Quadros et al, 2018). In Crucian carp (Carassius carassius), exposure to CAS elicits increases in serotonergic activity in the brainstem and optic tectum (Höglund et al, 2005), structures which have been involved in responses to distal and proximal threat (do Carmo Silva et al, 2018a). However, this only 3/39 happened when hiding material was unavailable in the tank.…”
Section: Introductionmentioning
confidence: 99%
“…However, this only 3/39 happened when hiding material was unavailable in the tank. In Nile tilapia (Oreochromis niloticus), CAS did not increase serotonergic activity in the dorsomedial and dorsolateral telencephali (Silva et al, 2015), homologues of the frontotemporal amygdaloid nuclei and hippocampus, respectively (do Carmo Silva et al, 2018a). These results suggest that, during or after exposure, CAS increases serotonergic activity in regions associated with "quick-and-dirty" behavioral responses to distal threat (a "fight/flight/freeze" or "fear" system), but not in the telencephalic areas associated with cautious exploration/risk assessment (a "behavioral inhibition" or "anxiety" system).…”
Section: Introductionmentioning
confidence: 99%